Prinsip Berkeadilan Tilang Elektronik dengan Sistem E-TLE (Studi Kota Yogyakarta) - Fuadhi Faktawan; Izzy Al Kautsar (Universitas Batanghari Jambi, 2022)
The development of ticketing system must be more dynamic to solve various problems of traffic violations. In Yogyakarta, an electronic based assessment method that began in mid-2020 managed to record 315 traffic violations, but the use of this electronic ticketing is still being rejected by some traffic users. The purpose of this study is to determine the effectiveness of the use of e-traffic ticketing which is applied in the legal area of Yogyakarta city and to analyze the aspects of justice in electronic ticket fines and measures of justice in the current practice of e-traffic tickets. This study uses a juridical normative research method with a statue approach approach and a concept approach. The result of this research is that the use of electronic tickets for law enforcement and motor vehicle drivers in the legal area of Yogyakarta City shows an increase in the aspect of order. For law enforcement, people who practice bribery are minimized, while for motorists it stimulates an orderly attitude in traffic. In the concept of justice, the use of electronic ticketing has paid attention to aspects of legal justice from the procedural formal side and aspects of substantive justice.